2015
DOI: 10.1080/10409289.2015.1009319
|View full text |Cite
|
Sign up to set email alerts
|

Child Vocabulary, Maternal Behavior, and Inhibitory Control Development Among Spanish-Speaking Children

Abstract: Research Findings The roles of child lexical diversity and maternal sensitivity in the development of young children’s inhibitory control were examined in 100 low-income Hispanic Spanish-speaking children. Child communication utterances at age 2½ years were transcribed from 10-min mother–child interactions to quantify lexical diversity. Maternal behavior was rated independently from the interactions. Inhibitory control was measured with a battery of tasks at ages 2½ and 3½. Greater maternal sensitivity was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 77 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…The second correlation was that between verbal ability and gender. The data for this correlation were provided in 12 of the included studies Blair et al, 2015;Carlson, Mandell, & Williams, 2004;Carlson & Meltzer, 2008;Carlson, Moses, & Claxton, 2004;Chang et al, 2015;Cuevas et al, 2014;Leve et al, 2013;Merz et al, 2016;Obradovic ´et al, 2016;Peredo et al, 2015;Poland et al, 2016). For these studies, the weighted correlation between verbal ability and gender is found to equal .11, reflecting a small female advantage in verbal ability.…”
Section: Alternative Explanationsmentioning
confidence: 99%
“…The second correlation was that between verbal ability and gender. The data for this correlation were provided in 12 of the included studies Blair et al, 2015;Carlson, Mandell, & Williams, 2004;Carlson & Meltzer, 2008;Carlson, Moses, & Claxton, 2004;Chang et al, 2015;Cuevas et al, 2014;Leve et al, 2013;Merz et al, 2016;Obradovic ´et al, 2016;Peredo et al, 2015;Poland et al, 2016). For these studies, the weighted correlation between verbal ability and gender is found to equal .11, reflecting a small female advantage in verbal ability.…”
Section: Alternative Explanationsmentioning
confidence: 99%
“…Research with monolingual children has shown that language (vocabulary size) and inhibitory control are correlated, in which the higher the vocabulary the better the inhibitory control. Verbal skills have been shown to positively relate to children's self-regulation abilities in early childhood (Fuhs & Day, 2011; Kuhn, Willoughby, Wilbourn, Vernon-Feagans & Blair, 2014; Peredo, Owen, Rojas & Caughy, 2015; Vallotton & Ayoub, 2011). In bilinguals, only the dominant language predicts IC.…”
Section: Introductionmentioning
confidence: 99%
“…The ratings have been used in different observational procedures, ranging from unstructured free-play situations to more structured goal-oriented tasks, and lasting from 5 minutes or less to 15 minutes or more (e.g., Maas, Vreeswijk, & van Bakel, 2013;Mills-Koonce et al, 2015;NICHD ECCRN, 2003;Towe-Goodman, Willoughby, Blair, Gustafsson, Mills-Koonce, & Cox, 2014). Various higher-order parenting quality constructs have been derived from these ratings using different approaches, including most typically a priori composites (e.g., Mills-Koonce et al, 2015;NICHD ECCRN, 1999;Peredo, Owen, Rojas, & Caughy, 2015).…”
mentioning
confidence: 99%